MATERIALS FOR A REVISION OF LAURACEAE III - KOSTERMANS, A. J. G. H. (REINWARDTIA, 1970)
1. In this paper a total of 153 species of Lauraceae (not including the 96 species reduced to synonymy) are discussed. 2. New species are described in Alseodaphne (1), Beilschmiedia (6), Cinna in.omM.7n (23), Cryptocarya (3), Endiandra (3), Lindera (1), Litsea (24), Persea (2) and Phoebe (4). 3. New combinations are proposed in Beilschmiedia (2), Endiandra (1) and Litsea (3). 4. New names are coined for species of Beilschmiedia (1), Cinnamomum (2)and Litsea (2). 5. Reductions are made in Actinodaphne (5), Alseodaphne (1), Beilschmiedia.(5), Cinnamomum (45), Endiandra (3), Lindera,(1),Litsea -(11),Machilus(1), Neolitsea (3),Persea (2), Phoebe (4), Tetradenm (3) and Tetranthera (11). 6. Beilschmiedia maingayi Hook, f., Cinnamomum siibavenium Miq., Litsea artocarpifolia Gamble and L. castanea Hook. f. are recorded for the first time for Java.